Brain anomaly networks uncover heterogeneous functional reorganization patterns after stroke - Yong Zou; Zhiyong Zhao; Dazhi Yin; Mingxia Fan; Michael Small; Zonghua Liu; Claus C. Hilgetag; Jürgen Kurths (NeuroImage: Clinical, 2018)
Stroke has a large physical, psychological, and financial burden on patients, their families, and society. Based on functional networks (FNs) constructed from resting state fMRI data, network connectivity after stroke is commonly conjectured to be more randomly reconfigured. We find that this hypothesis depends on the severity of stroke. Head movement-corrected, resting-state fMRI data were acquired from 32 patients after stroke, and 37 healthy volunteers. We constructed anomaly FNs, which combine time series information of a patient with the healthy control group. We propose data-driven techniques to automatically identify regions of interest that are stroke relevant. Graph analysis based on anomaly FNs suggests consistently that strong connections in healthy controls are broken down specifically and characteristically for brain areas that are related to sensorimotor functions and frontoparietal control systems, but new links in stroke patients are rebuilt randomly from all possible areas. Entropic measures of complexity are proposed for characterizing the functional connectivity reorganization patterns, which are correlated with hand and wrist function assessments of stroke patients and show high potential for clinical use. Keywords: Brain networks, Random reorganization hypothesis, Connectivity complexity, Stroke